Monitoring of Water Bodies and Non-vegetated Areas in Selenica ‑ Albania with Sar and Optical Images - Belba, Pietro; Kucaj, Spartak; Thanas, Jorgaq (Geomatics and Environmental Engineering, 2022)
The availability of Sentinel satellites for providing open data with optical and SAR imagery leads to better opportunities related to Earth surface mapping and monitoring. Recently, optical fusion with radar data has shown improvement in classification quality and the accuracy of information acquired. In this setting, the main objective of this research is to monitor the environmental impact of an open-pit mine on water, vegetation, and non-vegetation areas by exploring the single and combined use of Sentinel-1 and Sentinel-2 data. The data utilized in this paper were collected from the European Space Agency Copernicus program. After selecting the Selenica region, we explored the products in the Sentinel Application Platform. According to our data, Sentinel-2 misses the small water ponds but successfully identifies the river and open-pit areas. It mistakenly identifies urban structures and cloud areas as non-vegetated and does not identify non-vegetated areas which correspond to mining operation areas. Sentinel-1 identifies very small water ponds and delivers additional information in the cloudy areas, but misses a part of the river. Alongside the strong contribution in identifying the vegetation, it also roughly identifies the non-vegetation areas of mining operations.